Oil and Gold Return Spillover Effect on The Elasticity of Stock Markets - Bani-Khalaf, Omar Abdallah Ahmad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This dissertation aimed to achieve two primary goals. First, I studied the elasticity spillover effect in the Middle East financial market. Second, I studied the return spillover effect of oil and gold on the elasticity of financial markets in a group of Middle Eastern countries. To achieve these goals, I used the latest method to test the time effect during time variation. For instance, I employed bivariate and partial wavelet tests to visualize the association and the effect during the time domain. The results indicated an interaction between oil-exporting countries, while it is less for importing countries. The Saudi market is also the largest source for determining the elasticity of the Middle East markets. The Jordanian, Turkish, and Kuwaiti markets are the most affected by the elasticity of the region's markets. Finally, the Bahraini market is considered one of the financial markets least influenced by the elasticity of the region's markets. In contrast, the Egyptian and Bahraini markets interact the least with the other financial markets in the Middle East. Moreover, I found a heterogeneous impact of oil and gold returns on stock market elasticity. In contrast, oil returns significantly affected elasticity in most oilexporting countries. Additionally, the elasticity of financial markets in oil-importing countries only slightly impacted the movement of oil returns. The impact of oil and gold returns also varied among short, medium, and long-term periods; gold returns were greater for Kuwait, Bahrain, Saudi Arabia, and Jordan. Additionally, the impact of oil was more in Qatar, Bahrain, and Egypt, whereas the effect of gold and oil was equal in Turkey. Lastly, the COVID-19 pandemic significantly affected the elasticity of financial markets.

ÖZ: Bu tez iki temel amaca ulaşmayı amaçlamıştır. İlk olarak, Orta Doğu finans piyasasındaki esneklik yayılma etkisini inceledim. İkinci olarak, bir grup Ortadoğu ülkesinde petrol ve altının finansal piyasaların esnekliği üzerindeki getirisinin yayılma etkisini inceledim. Bu hedeflere ulaşmak için, zaman değişimi sırasında zaman etkisini test etmek için en son yöntemi kullandım. Örneğin, zaman alanı boyunca ilişkiyi ve etkiyi görselleştirmek için iki değişkenli ve kısmi dalgacık testleri kullandım. Sonuçlar, petrol ihraç eden ülkeler arasında bir etkileşime işaret ederken, ithalatçı ülkeler arasında daha az etkileşim olduğu gösterilmiştir. Suudi pazarı aynı zamanda Orta Doğu pazarlarının esnekliğini belirleyen en büyük kaynaktır. Ek olarak, bölge piyasalarının esnekliğinden en çok Ürdün, Türkiye ve Kuveyt piyasaları etkilenmektedir. Son olarak, Bahreyn piyasası, bölge piyasalarının esnekliğinden en az etkilenen finansal piyasalardan biri olarak kabul edilmektedir. Buna karşılık, Mısır ve Bahreyn piyasaları, Orta Doğu'daki diğer finansal piyasalarla en az etkileşime giriyor. Ayrıca, petrol ve altın getirilerinin borsa esnekliği üzerinde heterojen bir etkisi buldum. Buna karşılık, petrol getirileri, petrol ihraç eden çoğu ülkedeki esnekliği önemli ölçüde etkiledi. Ek olarak, petrol ithal eden ülkelerdeki finansal piyasaların esnekliği, petrol getirilerinin hareketini çok az etkilemiştir. Petrol ve altın getirilerinin etkisi de kısa, orta ve uzun vadeli dönemler arasında değişmektedir; Altın getirileri Kuveyt, Bahreyn, Suudi Arabistan ve Ürdün için daha fazla olduğu belirtilmiştir. . Ayrıca Katar, Bahreyn ve Mısır'da petrolün etkisi daha fazlayken, Türkiye'de altın ve petrolün etkisi eşittir. Son olarak, COVID-19 salgını finansal piyasaların esnekliğini önemli ölçüde etkilemektedir.
Doctor of Philosophy in Finance. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2022. Supervisor: Asst. Prof. Dr. Nigar Taşpınar
Keywords: Thesis Tez